KARAKTERISTIK OIL SHALE DI KAWASAN BUKIT SUSAH, RIAU - Hermiyanto, Muhammad Heri; Panggabean, Hermes (Pusat Survei Geologi, 2008)
Oil shale, as an alternative energy resource, is recognized in the Eocene - Oligocene Kelesa Formation, located in theBukit Susah area, within the Central Sumatera Basin, of the back-arc type. An almost complete rock sequence of the86.8 m thick part of oil shale-bearing formation, found in the Puti Kayu River, comprises an association of shale with carbonaceous siltstone, sandstone, conglomeratic sandstone, and conglomerate. The thickness of shale bed is approximately 27.90 meter. Oil shale in the study area is potential as an oil-gas prone source rock, within good to excellent category, containing Kerogen Types I and II.. The dominant maceral group is exinite, composed of alginite (0.4- 0.6 %), resinite (0.4 - 2.0 %), sporinite (0.4 - 0.8 %), suberinite (0.4 - 2 %), cutinite (0.6 - 1.4 %), and exsudatinite (0.2 - 0.6 %); whilst the minor one is vitrinite ranging from 0.6 - 7.6 %. The average value of vitrinite reflectance varies from 0.27 to 0.43 %. Thermal maturity level of the oil shale, in general, is situated within the immature category, although it tends to be close to the immature - mature boundary line, beyond oil birth line. Clay minerals consist of smectite-illite assosiation, with illite and kaolinite. The shale has undergone a diagenetic process within an early diagenetic level. A palynological study shows that the age of the oil shale in Bukit Susah is Middle to Late Eocene. Keywords: oil shale, alternative energy, Eocene-Oligocene , Bukit Susah, oil-gas prone